2018
DOI: 10.1105/tpc.18.00155
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Acetyltransferase NSI Is Required for State Transitions in Arabidopsis thaliana

Abstract: The amount of light energy received by the photosynthetic reaction centers photosystem II (PSII) and photosystem I (PSI) is balanced through state transitions. Reversible phosphorylation of a light-harvesting antenna trimer (L-LHCII) orchestrates the association between L-LHCII and the photosystems, thus adjusting the amount of excitation energy received by the reaction centers. In this study, we identified the enzyme NUCLEAR SHUTTLE INTERACTING (NSI; AT1G32070) as an active lysine acetyltransferase in the chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 74 publications
6
95
0
Order By: Relevance
“…GO enrichment of biological processes involved in light harvesting and photosynthesis (Data S9) further supports the known role of protein phosphorylation and acetylation in the regulation of photosynthesis (Reiland et al ., ; Finkemeier et al ., ; Hartl et al ., ). Previous studies have reported that light‐harvesting and photosynthesis proteins are regulated by either phosphorylation (Longoni et al ., ; Baginsky, ; Allen, ) or acetylation (Hartl et al ., ; Koskela et al ., ). Our data show when, and on which proteins, these PTMs intersect (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…GO enrichment of biological processes involved in light harvesting and photosynthesis (Data S9) further supports the known role of protein phosphorylation and acetylation in the regulation of photosynthesis (Reiland et al ., ; Finkemeier et al ., ; Hartl et al ., ). Previous studies have reported that light‐harvesting and photosynthesis proteins are regulated by either phosphorylation (Longoni et al ., ; Baginsky, ; Allen, ) or acetylation (Hartl et al ., ; Koskela et al ., ). Our data show when, and on which proteins, these PTMs intersect (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…The diurnal fluctuations in the abundance that we find for both protein phosphorylation and acetylation events on light‐harvesting and photosystems proteins suggest that these proteins represent key intersecting nodes of signaling and metabolism. Only a single lysine deacetylase (AtHDA14, At4g33470) and three acetyltransferases (AtGNATa, At3g54610; AtCBPc, At1g55970; and NSI1, At1g32070) have been identified as plastidial (Hartl et al ., ; Uhrig et al ., ; Koskela et al ., ), suggesting that substrate specificity for these enzymes must be achieved through the formation of specific but currently unknown protein complexes similar to phosphoprotein phosphatase (PPP)‐family phosphatases (Uhrig et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, acetylation of the PsaH protein, in very close proximity to this additional dimer, was found to be essential for state transitions. The loss of this acetylation, though, induced the loss of the classic, well known PSI–LHCII supercomplex, suggesting instead a role in LHCII binding (Koskela et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…When forming the experimental data for use in FAT‐PTM from PhosPhAt 4.0, phosphorylation site predictions were omitted due to a lack of spectral support by only accounting for modified peptide sequences that had precisely mapped phosphorylation events indicated by (pS), (pT) and (pY). The additional data encompassed in FAT‐PTM, including modification type, localization site and total number of spectral observations supporting each PTM site, were collected from published studies in the literature (Miller et al ., , ; Hemsley et al ., ; Kim et al ., ; Svozil et al ., ; Hu et al ., ; Johnson and Vert, ; Walton et al ., ; Xu et al ., , ; Koskela et al ., ; Liu et al ., ; Majeran et al ., ; Rytz et al ., ; Zeng et al ., ). For quantitative phosphoproteomics studies, abundance fold‐change information for phosphopeptides based on ratiometric quantification of isobaric tag or stable isotope reporters was also collected from supplemental files in the following references (Benschop et al ., ; Nühse et al ., ; Mithoe et al ., ; Zhang et al ., , ; Chen and Hoehenwarter, ; Minkoff et al ., ; Roitinger et al ., ; Cho et al ., ; Bhaskara et al ., ; Wang et al ., ).…”
Section: Methodsmentioning
confidence: 99%